Wigner's friend's memory and the no-signaling principle - Veronika Baumann; Časlav Brukner (Quantum)
The Wigner's friend experiment is a thought experiment in which a so-called superobserver (Wigner) observes another observer (the friend) who has performed a quantum measurement on a physical system. In this setup Wigner treats the friend, the system and potentially other degrees of freedom involved in the friend's measurement as one joint quantum system. In general, Wigner's measurement changes the internal record of the friend's measurement result such that after the measurement by the superobserver the result stored in the observer's memory register is no longer the same as the result the friend obtained initially, i.e. before she was measured by Wigner. Here, we show that any awareness by the friend of this change of her memory, which can be modeled by an additional register storing the information about the change, conflicts with the no-signaling condition in extended Wigner-friend scenarios.